Phonological Challenges Faced by Shina ESL Speakers in Gilgit-Baltistan: An Exploratory Study - Kaneez Fatima; Sajid Hussain; Moin Ud Din; Sohbat Ali (Social Science Review Archives, 2025)
The present study has explored the phonological issues which create hindrance for the Shina native speakers while learning English as a second language. The study has considered those English consonant sounds which are not present in Shina native language because Shina speakers frequently face mispronunciation problems while learning English as a second language. These hindrances regarding pronunciation preclude them not only from their expected proficiency in language but also affect the auditory and oral skills in the target language. The data was collected through questionnaires and interviews from the undergrad students studying at Karakoram International University. The obtained data were statistically analyzed through the software Praat. The results revealed that five English consonant phonemes; the post-alveolar voiced fricative /ʒ/, the dental voiceless fricative/θ/, the labiodental voiced less fricative/f/, the labiodental fricatives/v/, palate- alveolar /ð/, were creating problems for Shina speakers. It was also observed that the speakers used appropriate sounds of Shina language like /dz/,/t/,/d/,/ph/, and /w/ to replace the English phonemes. The reasons behind the problems faced by Shina speakers while learning a second language included: interference of mother tongue, the difference in the sound systems of English and Shina, medium of instruction in schools and colleges, lack of trained language teachers, and lack of motivation. To counter these issues, it is suggested that the audio-lingual method should be used to eradicate the phonological problems among the ESL learners of the Shina language.